New Business Model for Furniture Manufacturing Companies Using the Concept of Design Thinking (Case Study of PT Multi Suplai International) - Arif Rahman Yudiantoro (Riviera Publishing, 2025)
The implementation of made-to-order systems in business can pose problems in the future, especially when companies rely on intermediaries such as distributors and e-commerce platforms to sell their products. PT Multi Suplai International, a furniture manufacturer that implements a made-to-order system as a production strategy, experienced a negative impact due to changes in e-commerce platform policies in 2022. The new policy accelerates the delivery time limit of products from sellers to shipping companies, which has an impact on declining sales profits and production quality. This research aims to identify a new business model that is suitable for PT Multi Suplai Internasional with the Indonesian market conditions using a design thinking process that emphasizes empathy to consumers, defining consumer needs, making business model ideas, making business model prototypes, and testing new business models. Through this approach, a new business model, which is made-to-stock, was chosen. The detailed implementation plan was developed using a new business model canvas for PT Multi Suplai International.